Routledge handbook of heritage in Asia - Daly, Patrick T., 1975-; Winter, Tim, 1971- (Milton Park, Abingdon, Oxon : Routledge, 2012)
'Across Asia today rapid economic and social change means the region's heritage is at once under threat and undergoing a revival as never before. This volume examines heritage as a key component in the unfolding modernities of Asia, moving between analytical scales to address questions of tourism, urban planning, national or ethnic expressions of identity, conflict memorialisation, and biodiversity. For some, heritage has become an effective means for protecting those landscapes, rituals, artefacts or traditional values endangered by rapid socio-economic change. For others, it has emerged as a valuable resource for achieving wider goals such as poverty alleviation, nation building or the cultural profiling of citizens. In certain instances however, heritage protection represents an obstacle inhibiting progress, national unification, or the shedding of unwanted memories. The Routledge Handbook of Heritage in Asia offers an expansive account of the complexities of heritage in relation to a series of wider historical, socio political, environmental and physical changes. The international team of contributors take an interdisciplinary approach and present both new challenges and new directions for our understanding of contemporary Asia. With chapters covering the entire region, this Handbook will be of interest across a wide range of disciplines including: heritage studies, Asian studies, cultural sociology, religious studies, and social policy in Asia.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Cultural property -- Asia; Historic preservation -- Asia; Heritage tourism -- Asia; Asia -- Civilization